Handbook of Research on the Empirical Aspects of Strategic Trade Negotiations and Management - Crespo, N.; Simões, N. (2021)
International trade is a key dimension of the world economy, it is a critical factor in raising living standards, increasing employment, and providing a larger variety of goods to consumers around the world. Despite the strong focus that international trade research has received in theoretical terms, the empirical aspects of trade are less clear and justify further research. In this context, it is essential for studies to focus on shedding light on the most important methods used to evaluate the multiple dimensions of trade within this international context. Trade has a myriad of direct and indirect effects, therefore touching several fields of research, including economics, management, finance, international relations, political science, and sociology, which makes it essential to explore. The Handbook of Research on the Empirical Aspects of Strategic Trade Negotiations and Management provides a systematic overview of the latest trends in the empirical analysis of trade from international perspectives. It provides a survey on the methods used to evaluate a specific topic in international trade, enhance knowledge about the multiple facets of international trade around the world, and grant in-depth surveys of previous empirical findings on specific topics in international trade. Important topics covered within this book include trade diversification, regional centrality, ethical pricing, globalization, cultural impacts, and open economies. This book is a valuable reference tool for government officials, policy makers, managers, executives, economists, practitioners, stakeholders, researchers, academicians, and students.